(untitled) (UNED Research Journal, 2021)
Introduction: Sloths are arboreal mammals that defecate on the ground, increasing the risk of predation. There are several hypotheses that try to explain why they undergo this risk. Objective: To critically review all the hypotheses and to propose a new hypothesis that is compatible with all known data. Methods: I verified the assumptions and implications of five hypotheses against the literature available February, 2021. Results: Previous hypotheses either lack reliable supporting data, or are contradicted by published data. Here I propose that defecation on the ground is an ancestral behavior that persists in all sloth species because there has not been enough natural selection against it. Conclusions: Current knowledge of sloth biology is compatible with the hypothesis that there has not been enough selective pressure for sloths to abandon defecation on the ground.